Fungsi Peta Rencana Hidup sebagai Sarana Aktualisasi Diri Warga Binaan di Lapas Kelas IIA Purwokerto dalam Perspektif Hierarki Kebutuhan Maslow - Khusni Matoyah (UIN Kiai Haji Achmad Siddiq Jember, 2025)
The process of rehabilitating correctional inmates (WBP) plays an important role in helping them readapt to society after serving their sentence. This research aims to examine how the Life Plan Map can help inmates design their future and achieve self-actualization based on Maslow's hierarchy of needs theory. This study uses a descriptive qualitative method, with data collection techniques through in-depth interviews and observations at Purwokerto Class IIA Prison. The subjects of the research are inmates who participated in the Life Plan Map preparation activities. The research results show that this tool helps enhance self-awareness, identify obstacles, and formulate concrete steps to meet basic to psychological needs, ultimately supporting the achievement of self-actualization. Thus, the Life Plan Map can be a beneficial approach in supporting the social reintegration and personal development of inmates in accordance with Maslow's hierarchy of needs.